2018
DOI: 10.1136/jnnp-2017-317492
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of exosomal miR-204-5p and miR-632 as a biomarker for FTD: a GENFI study

Abstract: Objective To determine whether exosomal microRNAs (miRNAs) in CSF of patients with FTD can serve as diagnostic biomarkers, we assessed miRNA expression in the Genetic FTD Initiative (GENFI) cohort and in sporadic FTD. Methods GENFI participants were either carriers of a pathogenic mutation in progranulin (GRN), chromosome 9 open reading frame 72 (C9orf72) or microtubule-associated protein tau (MAPT), or were at risk of carrying a mutation because a first-degree relative was a known symptomatic mutation carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
2
53
3
Order By: Relevance
“…Genetic FTD is preceded by a long period in which, despite the evidence of initial changes in biomarkers and brain structure, behaviour and cognition are spared. [17,[19][20][21] Pharmacological and non-pharmacological interventions may provide better clinical outcomes if applied in this phase, when the brain can still cope with pathology processes, and such treatments may eventually delay disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic FTD is preceded by a long period in which, despite the evidence of initial changes in biomarkers and brain structure, behaviour and cognition are spared. [17,[19][20][21] Pharmacological and non-pharmacological interventions may provide better clinical outcomes if applied in this phase, when the brain can still cope with pathology processes, and such treatments may eventually delay disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an in vitro model of prion disease identified at least 17 miRNAs that were dysregulated in EVs derived from prion‐infected neurons compared to uninfected neurons (Bellingham, Coleman, & Hill, ), while three miRNAs were upregulated in CSF EVs isolated from patients with acute encephalitis syndrome due to infection with Japanese Encephalitis virus (Goswami et al, ). Decreased EV‐packaged miR‐205‐5p and −632 was also recently observed in the CSF of individuals with symptomatic frontotemporal dementia, compared to presymptomatic and healthy controls (Schneider et al, ). Taken together, these studies provide potential clinical utility in using EV miRNA levels as clinically relevant biomarkers for a variety of CNS disorders.…”
Section: Extracellular Vesicle Localized Mirnas As Biomarkers For Cnsmentioning
confidence: 70%
“…(2020) 10:3341 | https://doi.org/10.1038/s41598-020-60133-z www.nature.com/scientificreports www.nature.com/scientificreports/ function 21 . Notably, miR-204-5p which was downregulated in chronic TBI was also reported downregulated in frontotemporal dementia 22 , a finding that suggests that this miRNA might serve as a useful biomarker of early stage, subclinical dementia in neurodegenerative disorders. TBI-dysregulated miRNAs also regulate multiple genes involved in neurodevelopmental functions 23 ; Schork et al, showed in their study of shared risk across psychiatric disorders, that all share dysregulated expression of common gene variants that regulate neural development 24 .…”
Section: Discussionmentioning
confidence: 91%